Forging the golden urn: the Qing Empire and the politics and the politics of reincarnation in Tibet - Oidtmann, Max (Studies of the Weatherhead East Asian Institute, Columbia University, 2018)
The royal regulations -- Shamanic colonialism -- Amdowas speaking in code -- Conclusion : paradoxes of the urn and the limits of empire